Altas habilidades/superdotação e acadêmicos idosos: o direito à identificação - Costa, Leandra Costa da (2016)
This dissertation is associated to the doctoral program in Education from the Graduation Program in Education from the Federal University of Santa Maria (UFSM) and belongs to the Research Line LP3 Special Education. The relevance and need of this study proposal lies on the fact that there are no studies on high abilities/gifted (HA/G) directed to the identification of elderly people and also in the lack of theoretical contributions that support this discussion. The objective of this study was to identify HA/G in elderly scholars inserted in the undergraduate program of the Federal University of Santa Maria, located in Rio Grande do Sul (RS) in order for them to be able to recognize themselves with indicators and characteristics of HA/G) and receive educational service consistent with their needs. Thus, it was developed a tool that allowed the identification of HA/G in elderly scholars in order to facilitate their insertion the social and academic environment. This qualitative research is characterized as a case study. The participants of this investigation were eight scholars that were more than 60 years old, who entered UFSM through vestibular for attending mode , and that are nowadays regular students of the institution in the graduation courses. Following a theoretical framework that serves as basis for the study and the data collected, categories of analysis were selected based on the premises of Content Analysis (BARDIN, 2011). Among the instruments that were part of this study, there is the individual questionnaire used to identify the indicators of HA/G in Elderly People (QIIAHSDI), adapted from Pérez (2008), that went through a process of validation previous to its application, a Personal Information Form (PIF) used in order to obtain personal, family, work, and leisure activities information, and also a semi-structures interview. Many of the common indicators found in the studies carried out with adults cited by Pérez (2008) and Delpretto (2009) were noticed in the elderly participants, such as curiosity, creativity, leadership, persistence, high sense of humor, autonomy, and preference for challenges. The identification of elderly people will favor adequate educational alternatives and recognition of their behaviors and potentialities, since it is a necessity to identify them, favoring their understanding according to their personal, intelectual, and emotional characteristics linked to HA/G.